Implementation of Environmental Education Based on Madura Local Wisdom to Increase Student Scientific Literacy - Yamin, Yamin; Qomaria , Nur; Hartiningsih , Try; Pramudista , Hina Tria; Asyroful Ibad, Muhamad (LPPM Universitas PGRI Semarang, 2024)
Environmental Education is a lecture process that provides insight to students regarding the understanding and awareness of the environment as a means of sustainable development. Environmental education lectures can be used as a means to improve students' science literacy skills. Science literacy skills can increase in learning associated with local wisdom. Local wisdom has an important relationship with education, this is important for the development of education, so the educational process must be conducive to connecting learning with the environment. Therefore, local wisdom needs to be associated with learning, one of which is with environmental education lectures. The purpose of this research is to improve students' science literacy skills applied to Environmental Education lectures based on Madura local wisdom. This research is a quantitative descriptive research. Data collection techniques include observation, interviews, documentation and tests. Then, the data obtained was analyzed using quantitative descriptive data analysis. The results showed that science literacy in the science process domain for indicators identified scientific problems by 7.6%, explained scientific phenomena by 7.4%, and used scientific evidence by 66%. The achievement of science literacy in the science content domain was 78% (good category). Science literacy in the realm of students' attitudes towards science as a whole reached 76.3% (good category). The average result of students' overall science literacy achievement was 72% (sufficient category). Based on the results of the study, it can be concluded that research on the Implementation of Environmental Education Lectures Based on Madura Local Wisdom to Improve Student Scientific Literacy can improve students' science literacy skills and teach environmental conservation and local wisdom on Madura Island